2020
DOI: 10.1007/s40618-020-01258-w
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetry indicates more severe and active disease in Graves’ orbitopathy: results from a prospective cross-sectional multicentre study

Abstract: Purpose Patients with Graves’ orbitopathy can present with asymmetric disease. The aim of this study was to identify clinical characteristics that distinguish asymmetric from unilateral and symmetric Graves’ orbitopathy. Methods This was a multi-centre study of new referrals to 13 European Group on Graves’ Orbitopathy (EUGOGO) tertiary centres. New patients presenting over a 4 month period with a diagnosis of Graves’ orbitopathy were included. Patient demographics were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 26 publications
(43 reference statements)
2
23
0
Order By: Relevance
“…However, some patients might exhibit asymmetric or unilateral symptoms, for yet unknown reasons. It has been suggested that unilateral GO may progress to bilateral disease ( 11 ) and we have also found that asymmetry was associated with more severe and active GO ( 12 ). Asymmetry and/or unilateral GO can impose diagnostic challenges ( 13 ) and it is therefore important that awareness for asymmetric GO be raised.…”
Section: Introductionsupporting
confidence: 64%
See 1 more Smart Citation
“…However, some patients might exhibit asymmetric or unilateral symptoms, for yet unknown reasons. It has been suggested that unilateral GO may progress to bilateral disease ( 11 ) and we have also found that asymmetry was associated with more severe and active GO ( 12 ). Asymmetry and/or unilateral GO can impose diagnostic challenges ( 13 ) and it is therefore important that awareness for asymmetric GO be raised.…”
Section: Introductionsupporting
confidence: 64%
“…In our recently published study, asymmetry was defined as bilateral disease with one or more of the following features: difference between the two eyes in exophthalmos by ≥2 mm; difference in palpebral aperture by ≥2 mm; difference in eyelid swelling by ≥1 grades; difference in eyelid erythema by ≥1 grades; difference in conjunctival redness by ≥1 grades; presence of dysthyroid optic neuropathy in one eye only. Unilateral disease was defined as one or more clinical features of GO in one eye without any evidence of GO in the contralateral eye ( 12 ). Moreover, disease severity is assessed similarly to bilateral disease, using clinically evaluated standardized tools, such as CAS ( 27 ) and Vision, Inflammation, Strabismus, Appearance (VISA) ( 28 ).…”
Section: Assessment Of Asymmetric And/or Unilateral Gomentioning
confidence: 99%
“…Asymmetric forms have been described in 4-14% of cases, unilateral forms in 9-34% of cases (9,(32)(33)(34). In a recent multicenter study of 269 patients referred to EUGOGO centers, although the majority (157 patients, 58%) had symmetric GO, many patients had either asymmetric or unilateral GO (26) (Figure 3). Interestingly, patients in the asymmetric group were older, were more frequently men, and tended to have more severe and active GO than the other groups (26).…”
Section: Phenotypementioning
confidence: 99%
“…In a recent multicenter study of 269 patients referred to EUGOGO centers, although the majority (157 patients, 58%) had symmetric GO, many patients had either asymmetric or unilateral GO (26) (Figure 3). Interestingly, patients in the asymmetric group were older, were more frequently men, and tended to have more severe and active GO than the other groups (26). The reasons for asymmetric presentation of GO are unknown, but they might include differences in the anatomy of bony orbit or its vascularization.…”
Section: Phenotypementioning
confidence: 99%
See 1 more Smart Citation